The Girl Who Kicked the Hornet's Nest - Book 3 - Larsson, Stieg 1954-2004.; Keeland, Reg 1943- (New York : Vintage Books / Black Lizzard, 2009)
While recovering in the hospital, Lisbeth Salander enlists the aid of journalist Mikael Blomkvist to prove her innocent of three murders and identify the corrupt politicians who have allowed her to suffer.
Originally published: London : MacLehose Press, 2009.
Sequel to: The girl who played with fire.
Keywords: Political corruption -- Fiction -- Sweden; Revenge -- Fiction; Fiction